IMPLEMENTASI KOMUNIKASI GERAK TUBUH PADA MAHASISWA BIMBINGAN PENYULUHAN ISLAM - Salsabila Salsabila; Nasichah Nasichah; Salsa Nur Haliza; Maghfy Ray Ramadhan Husny (CV. ADIBA AISHA AMIRA, 2023)
The implementation of gesture communication is an important aspect in various contexts of human communication. Gestures, facial expressions, and body language as a whole can convey powerful messages, reinforce social interactions, and influence the perceptions of others. In this abstract, researchers will discuss the implementation of gesture communication for Islamic Guidance and Counseling students at UIN Syarif Hidayatullah Jakarta, the purpose of this study is to find out how gesture communication can be implemented for Islamic Guidance and Counseling students in their daily lives. The research method used is quantitative with data collection techniques, namely using a questionnaire. Based on the results of the study, it can be seen that gesture communication such as how he stands, walks, hand movements, touching actions, faces position, and eye contact when communicating has a significant impact on the effectiveness of gesture communication in Islamic Extension Guidance students at UIN Syarif Hidayatullah Jakarta. Gesture communication is also considered more reliable than verbal communication because the nature of nonverbal communication or gestures is a direct reflex or response.